Fatigue life analysis of natural fibres - Mohd Shamil, Shaari (2014)
Nowadays, the natural fibres are extensively used as cost-cutting in the materials and manufacturing industry. It is best to be considered as the most potential replacement for the glass fibres which are widely used in the market right now. The use of the natural fibres composites are due to two aspects, which are for environmental and economical in developing countries. Even though natural fibres have many advantages, due to their low-cost and low density, but they are not totally free of problems. Since very little is known about the. properties of these natural fiber composites, this thesis involves testing of those composites. The testing is done in two stages where the monotonic testing is performed first producing the stress-strain (a- e) diagram and tensile strength (UTS). Then, the loading parameters are designed for the fatigue life analysis to obtain the stress-life (S-N) curve. The textile architecture of the natural fibres also analyzed using CCD (charge-coupled device),, and the comparison between the natural fibres using polyethylene and polypropylene matrix are exhibited. From the results, it shows that the natural jute fibres using polypropylene matrix selected to be the best materials among the natural fibres where it satisfied the purpose of design as a good material not only to withstand stresses but also to be reliable and satisfy the fatigue life.